Design and modeling of line-tunneling field-effect transistors using low bandgap semiconductors - Chun-Hsing Shih (IEEE Publishing, 2024)
The low-bandgap engineering and line-tunneling architecture are the two major techniques to resolve the ON-current issues of tunnel field-effect transistors (TFETs). This paper elucidates the design and modeling of line-tunneling TFETs using low-bandgap materials. Three semiconductors, Ge, InAs, and InSb, are considered as examples to explore their physical operations and analytical models. 2-D device simulations were performed to examine the on/off characteristics. The appropriate operational voltages depend on the associated bandgap of semiconductors. The gate voltage should be larger than the bandgap voltage (E g /q) to ensure high ON-currents, whereas the drain voltage must be less than the bandgap voltage to control OFF-leakages. Because the minimum tunnel path has a key function in determining the tunneling in line-tunneling TFETs, the tunneling current is reformulated in terms of the minimum tunnel path with friendly compact forms. Two prime design factors, the source concentration and gate-insulator thickness, are examined both analytically and numerically, showing the minimum tunnel path can serve as a useful indicator for low-bandgap line-tunneling TFETs.